2022
DOI: 10.1002/da.23299
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of daily positive and negative affect and relations to anxiety and depression symptoms in a transdiagnostic clinical sample

Abstract: Background Despite interest in transdiagnostic dimensional approaches to psychopathology, little is known about the dynamic interplay of affecting and internalizing symptoms that cut across diverse mental health disorders. We examined within‐person reciprocal effects of negative and positive affect (NA, PA) and symptoms (depression and anxiety), and their between‐person associations with affective dynamics (i.e., affect inertia). Methods Individuals currently receiving treatment for psychological disorders (N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 76 publications
2
5
0
Order By: Relevance
“…This result is consistent with the findings of Stöber ( 2000 ), who suggested that negative prospective imagery may be more closely related to anxiety than to depression and that reduced vividness of positive prospective imagery may be more closely related to depression than to anxiety. It is also in line with the finding of Zhu et al ( 2022 ), which confirmed that daily negative affect has robust relationship with anxiety whereas daily positive affect has robust relationship with depression. Additionally, it is worth noting that the serial mediation effect in Model A was much greater than that in Model B.…”
Section: Discussionsupporting
confidence: 92%
“…This result is consistent with the findings of Stöber ( 2000 ), who suggested that negative prospective imagery may be more closely related to anxiety than to depression and that reduced vividness of positive prospective imagery may be more closely related to depression than to anxiety. It is also in line with the finding of Zhu et al ( 2022 ), which confirmed that daily negative affect has robust relationship with anxiety whereas daily positive affect has robust relationship with depression. Additionally, it is worth noting that the serial mediation effect in Model A was much greater than that in Model B.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with prior evidence showing that treatments focusing upon symptom reduction (e.g., CBT and pharmacotherapy) have little impact upon positive affect (Bosley et al, 2018; Craske et al, 2016; Dunn et al, 2020), including behavioral activation (Dichter et al, 2009; Moore et al, 2013). It also aligns with findings from a study examining daily affect and symptom dynamics (Zhu et al, 2022), which demonstrated that depression and anxiety symptoms did not predict subsequent positive affect during treatment in a partial hospital program. Perhaps positive affect is influenced more by reward processes (e.g., anticipation–motivation, response to reward attainment, and learning) than by symptom reduction.…”
Section: Discussionsupporting
confidence: 85%
“…Uncovering the dynamic processes of how positive and negative affect change in relation to depression and anxiety symptoms over the course of treatment may elucidate optimal treatment targets and thus refine treatment approaches. There is evidence that changes in both positive and negative affect predict subsequent depression symptom changes during CBT (Whelen & Strunk, 2021; Zhu et al, 2022). Conversely, there is evidence for changes in positive affect over the course of CBT to be contingent on decreases in depression (Kring et al, 2007) and anxiety (Bosley et al, 2018) symptoms, although Zhu et al (2022) did not find this effect.…”
Section: Negative Affectmentioning
confidence: 99%
See 1 more Smart Citation
“…Some Self-report questionnaires were primarily focused on comfortable, positive social touch, with less attention paid to those unpleasant, negative touch events such as the Positive Touch Experience Attitude Questionnaire (TEAQ) and the Tactile Biography (TBIO) (Beltran, Dijkerman, & Keizer, 2020;Trotter, McGlone, Reniers, & Deakin, 2018). However, in real world, negative affective states can be expressed via touch and closely linked to depression and anxiety (Saarinen, Harjunen, Jasinskaja-Lahti, Jääskeläinen, & Ravaja, 2021; Zhu et al, 2022). The Social Touch Questionnaire (STQ) was administered as a general measure of attitude toward social touch, covering a wide-ranging issue concerning positive, neutral and negative social contact in a relatively well-integrated manner (Wilhelm, Kochar, Roth, & Gross, 2001).…”
Section: Introductionmentioning
confidence: 99%